Repurposing the Pummerer Rearrangement: Determination of Methionine Sulfoxides in Peptides. (25th October 2019) - Woodroofe, Carolyn C.; Ivanic, Joseph; Monti, Sarah; Levine, Rodney L.; Swenson, Rolf E.
Abstract: The reversible oxidation of methionine residues in proteins has emerged as a biologically important post‐translational modification. However, detection and quantitation of methionine sulfoxide in proteins is difficult. Our aim is to develop a method for specifically derivatizing methionine sulfoxide residues. We report a Pummerer rearrangement of methionine sulfoxide treated sequentially with trimethylsilyl chloride and then 2‐mercaptoimidazole or pyridine‐2‐thiol to produce a dithioacetal product. This derivative is stable to standard mass spectrometry conditions, and its formation identified oxidized methionine residues. The scope and requirements of dithioacetal formation are reported for methionine sulfoxide and model substrates. The reaction intermediates have been investigated by computational techniques and by 13 C NMR spectroscopy. These provide evidence for an α‐chlorinated intermediate. The derivatization allows for detection and quantitation of methionine sulfoxide in proteins by mass spectrometry and potentially by immunochemical methods. Abstract : Oxidation of methionine residues in proteins is a biologically important post‐translational modification that is difficult to study. We show that activation of sulfoxides with TMSCl generates α‐chloro intermediates, which then react with specific thiols to generate dithioacetals. This modified Pummerer reaction can be used to study methionine sulfoxides in proteins.